Pelatihan Melukis One Stroke Painting bagi Kelompok Masyarakat Gondowangi Malang - Sultan Arif Rahmadianto; Yuyun Yuniati (University of Merdeka Malang, 2020)
The people of Gondowangi, Malang need a program to improve knowledge and skills art creations. One stroke painting is a simple painting technique that can produce unique and interesting visual works despite using only very simple techniques. Based on situation analysis, Ma Chung University created a corporate social responsibility program (CSR) aimed at empowering the people of Gondowangi, Malang in terms of knowledge and skills art creations. This program will be able to have a great influence on the people of Gondowangi, Malang, which is to make more productive and able to produce art products that have economic value. The method of this program is the first day is a socialization activity about the knowledge of painting with one stroke painting technique, then day two is a direct training activity painting with one stroke painting technique. The people are very enthusiastic to participate in this program. As a result of this program, the people of Gondowangi, Malang are more confident in painting and have art products. The sustainability of this program is excellent because has a consultation program that is coordinated directly between the head of this program and the head of people Gondowangi, Malang to ensure better cooperation in the future.DOI: https://doi.org/10.26905/abdimas.v5i2.4241